2022
DOI: 10.3390/ijerph192315492
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DNA Methylation of Clock Genes in Obese Adolescents after a Short-Term Body Weight Reduction Program: A Possible Metabolic and Endocrine Chrono-Resynchronization

Abstract: Circadian rhythms are generated by a series of genes, collectively named clock genes, which act as a self-sustained internal 24 h timing system in the body. Many physiological processes, including metabolism and the endocrine system, are regulated by clock genes in coordination with environmental cues. Loss of the circadian rhythms has been reported to contribute to widespread obesity, particularly in the pediatric population, which is increasingly exposed to chronodisruptors in industrialized society. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…showed that a short-term body weight reduction program induced a significant CLOCK hypermethylation together with a significant PER2 hypomethylation, suggesting that the body weight reduction program might result in beneficial cardiometabolic effects as well as in epigenetic remodelling of specific CLOCK genes. However, due to the experimental design, this study could not disclose whether epigenetic changes in CLOCK genes are cause or consequence of global cardiometabolic improvements ( 41 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…showed that a short-term body weight reduction program induced a significant CLOCK hypermethylation together with a significant PER2 hypomethylation, suggesting that the body weight reduction program might result in beneficial cardiometabolic effects as well as in epigenetic remodelling of specific CLOCK genes. However, due to the experimental design, this study could not disclose whether epigenetic changes in CLOCK genes are cause or consequence of global cardiometabolic improvements ( 41 ).…”
Section: Resultsmentioning
confidence: 95%
“…These studies analysed the methylation status of several genes related to immune response ( NFATC2IP & FKBP5 ) ( 36 , 38 ), mitochondrial function ( CPT1A ) ( 37 ) diabetes and ageing ( TXNIP & CAV1 ) ( 39 , 40 ), circadian rhythm ( CLOCK, CRY2 & PER2 ) ( 41 ) as well as obesity related genes (e.g. FTO ) ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity results in epigenetic alterations such as DNA methylation, which has been correlated with the future development of CRC and breast cancer [ 145 , 146 , 147 , 148 , 149 ]. The other main types of epigenetic changes include histone modifications and non-coding mRNA interference.…”
Section: Epigenetic Pathwaysmentioning
confidence: 99%